Cardiac computed tomography based analysis of mitral annulus, coronary sinus and left circumflex artery in patients with mitral regurgitation: Implications for transcatheter mitral annuloplasty techniques. (15th March 2023) - Lin, Fushun; Wang, Qian; Meng, Lingwei; Liang, Yongfeng; Kong, Xiangjin; Wei, Kaiming; Zhang, Qiuwang; Gu, Xinghua
Abstract: Introduction: CT imaging analysis of mitral annulus (MA), coronary sinus (CS) and left circumflex artery (LCX) is critical to transcatheter mitral annuloplasty (TMA), which, however, is scantly reported. We aimed to comprehensively assess MA, CS and LCX anatomy and geometry in mitral regurgitation (MR) based on 3-D reconstruction of cardiac CT images. Methods: Patients with primary or secondary MR and patients without MR were recruited and underwent cardiac CT examination. MR severity was evaluated by echocardiography. 3-D reconstruction of cardiac CT images was done by the Mimics Research 21.0 software. A MA-centered two dimensional coordinate system, a CS plane, a MA plane and a series of auxiliary planes along the posterior MA were created for the measurement of parameters defining MA, CS and LCX anatomy and geometry during the cardiac cycle. Results: The secondary MR group had a significantly higher MA perimeter index than the other two groups during the cardiac cycle. The CS diameters at most sites, and the posterior MA radian were substantially greater in the two MR groups. Distances between the CS and MA at some locations were significant different among the three groups. The secondary MR group had a significantly smaller CS-MA plane angle than the other two groups during systole, and than control group during diastole. The site where the CS crossed LCX was pinpointed. Conclusion: The comprehensive information from this study may help improve the results of TMA and enhance the design of devices for a better annuloplasty effect. Highlights: A comprehensive analysis of coronary sinus (CS), left circumflex artery (LCX) and mitral annulus (MA) anatomy and geometry in mitral regurgitation (MR) was performed by 3-D reconstruction of cardiac CT images. Secondary MR had a significantly greater MA perimeter than primary MR. A device with more than two anchors for indirect transcatheter mitral annuloplasty (ITMA) may be more effective in applying external circumferential pressure around the entire annulus for secondary MR. The majority of patients with secondary MR had a CS-MA plane angle <14.2 °, amenable to ITMA. To prevent LCX compression, extra caution should be taken while maneuvering and implanting devices at the AC and P1 planes where LCX crossed CS mostly. For a better annuloplasty effect, design of new devices should allow the radian formed by the arch between the two anchors of a device after ITMA to match the significantly increased MA radian in secondary MR.